THE STUDENTS’ VIEWS ON THE USE OF COMIC IN TEACHING AND LEARNING ENGLISH - Dicka Dwi Wicaksono; Sri Fatmaning Hartatik (Journey: Journal of English Language and Pedagogy, 2023)
This qualitative research is intended to find out students' views about whether comic media can be used as a medium for learning English. This research was conducted at SMPN 2 Dau Satu Atap involving 22 students of grade 7. The researcher as a key instrument used interviews to obtain the required data. Students were asked whether students had ever read comics; students' feelings when reading comics; and students' views on the use of comics as a medium for learning English. The data were obtained through interviews, then transcribed, read through, and classified student answers. The final finding, which was interpreted in terms of comics, was that there were 16 students who liked reading comics and 6 students who did not like comics. There are more than 73% of students in grade 7 who like to read comics and students say they are interested in using comic media as a medium for learning English.